O “ESPAÇO JOVEM” NA VIRADA DO SÉCULO: UM ESTUDO DA REVISTA ADVENTISTA (1993-2014) - SIQUEIRA, CHARLYS (2019)
The study of the relationship between youth and religion has been gaining ground in academic circles, especially in the social sciences and religion. This is due to the perception that examining this relationship may contribute to reflection on trends in social and religious behavior in the coming generations. The issue is also of interest to religious institutions as they recognize the constant and accelerating changes the world is going through and the need to articulate their symbolic universe for the young in order to preserve them in the church. The present work aims to understand how the religious institution in study perceives the needs of its young audience and how it seeks to supply them from the contents of its publications in the section "Young Space". This study thus focuses on a specific space from one of its official journals, the Adventist Review, at the turn of the century (1993-2014). The methodology adopted for this research consists of a review of the contemporary literature on youth and religion, followed by a documentary study focused on Adventist Magazine's "Young Space" from 1993 to 2014. The two main reasons for choosing this period are: (1) during this period of time the "Young Space" remained more stable in its editorial proposal and (2) it is also in this period that the turn of the century occurs bringing with it significant changes in the Brazilian religious framework according to the data made available by IBGE. In addition, the research will have a tracking of the main topics covered in the "Young Space" and an analysis of the frequency of its contents from the elaboration of graphs. In this way, this dissertation intends to contribute focusing on a specific publication in the field of Adventism and youth study.